Self Healing melalui Pendekatan Filsafat Dakwah: Studi tentang Paias Rohamu - Pane, Riem Malini; Lubis, Sufrin Efendi (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
This study aims to describe how the philosophy of paias rohamu in overcoming individual problems so that individuals are able to think positively, optimistically and hopefully. The research method used is a literature study. All data obtained are then compiled and studied carefully to solve the topics discussed. The results of this study indicate that. The philosophy of paias rohamu is one way that can be taken to overcome mental problems so that peace is created. This philosophy focuses on how an individual trains his mind to always think positively, always optimistically and hopefully in every activity that is carried out. The implications of this philosophy, first because the type of disease is abstract and starts from the mind so that it is very much in accordance with the focus of this motto which also trains the mind to always be optimistic. Second, this motto is easy to understand because it is local culture and is commonly applied in everyday life, it just needs to be arranged and tidied up so that it becomes a therapeutic tool that can be used to overcome abstract problems.